2003
DOI: 10.1007/s10156-002-0223-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of Japanese spotted fever and its aggravating factors

Abstract: Twenty-eight patients with Japanese spotted fever were clinically investigated. The diagnosis was determined by confirming an increase of specific antibody. All patients were treated with minocycline, and all recovered, excluding one patient with a fulminant course. Fever and exanthema were observed in all patients, and an eschar was pointed out in 20 (71%) patients. The platelet count was 10 x 10(4)/microl or lower in 8 (28%) patients. The fibrin degradation product (FDP)-level was abnormally high, 10 microg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 18 publications
0
49
0
4
Order By: Relevance
“…We estimate that hypercytokinemia may contribute to the disease severity of rickettsiosis, including JSF. For instance, fulminant TD has been associated with hemophagocytic syndrome (10), and this syndrome may represent a hyperreaction of the immune system mediated by an overactivated cytokine network during the advanced stages of rickettsial infection (19,(26)(27)(28). We previously reported that a downregulation of these cytokines and chemokines is observed after the administration of tetracyclines, demonstrated a correlation between the severity of TD and the serum concentration of TNF-␣ in the acute phase of the disease, and showed that TNF-␣ levels are predictive of the severity of TD (18,19,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…We estimate that hypercytokinemia may contribute to the disease severity of rickettsiosis, including JSF. For instance, fulminant TD has been associated with hemophagocytic syndrome (10), and this syndrome may represent a hyperreaction of the immune system mediated by an overactivated cytokine network during the advanced stages of rickettsial infection (19,(26)(27)(28). We previously reported that a downregulation of these cytokines and chemokines is observed after the administration of tetracyclines, demonstrated a correlation between the severity of TD and the serum concentration of TNF-␣ in the acute phase of the disease, and showed that TNF-␣ levels are predictive of the severity of TD (18,19,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Between 1984 and 2004, nine more species or subspecies of tick-borne spotted fever rickettsiae were identified as emerging pathogens throughout the world, including, R. japonica in Japan [6,46,65,71,72,[82][83][84]146]; "R. conorii caspia" in Astrakhan [35,38,39,143], Africa [47] and Kosovo [48]; R. africae in sub-Saharan Africa and the West Indies [62,63]; R. honei in the Flinders Island, offshore of Australia [9,57,140,141], the Island of Tasmania, Australia [153], Thailand [73], and possibly in the USA [13]; R. slovaca in Europe [29,74,101,122]; "R. sibirica mongolotimonae" in China [157], Europe [44,118] and Africa [106,113]; R. heilongjiangensis in China [42,49]; R. aeschlimannii in Africa [11,112,121] and Europe [43]; and finally R. parkeri in the USA [104]. R. helvetica is also suspected to be a human pathogen in Europe [45] and Asia [46,61,107], but this needs c...…”
Section: Tick-borne Rickettsiosesmentioning
confidence: 99%
“…Tick-borne SFG rickettsioses range from mild to severe and fatal disease. To date, no mortalities or severe complications have been reported in patients with African tick-bite fever caused by R. africae [62], whereas severe disease, including one fatal case, has been reported with Japanese spotted fever rickettsioses [6,71,72,84].…”
Section: Tick-borne Rickettsiosesmentioning
confidence: 99%
“…Fluoroquinolones may be needed to completely eradicate the causative rickettsiae. Moreover, fluoroquinolones should be administered as soon as antibiotics are deemed ineffective and rickettsial diseases are strongly suspected, because some spotted fever-type rickettsial diseases including Japanese spotted fever, can be fatal (1,2,13).…”
Section: Pus (4) the Half-life Of Ciprofloxacin Is Very Short (26 Hrmentioning
confidence: 99%
“…For several days after1984, severe cases have been sporadically reported, however, most cases were cured by tetracyclines (1)(2)(3). Kodama et al reported twenty-eight patients with Japanese spotted fever were treated with minocycline, and all recovered, excluding one patient with a severe course (2). We encountered a patient with severe Japanese spotted fever who was not cured by tetracycline, but treated successfully with fluoroquinolone.…”
Section: Introductionmentioning
confidence: 99%